Drug therapy for alcohol dependence in primary care in the UK: A Clinical Practice Research Datalink study - Thompson, Andrew (PLoS One, 2017)
AIM: To evaluate drug therapy for alcohol dependence in the 12 months after first diagnosis in UK primary care. DESIGN: Open cohort study. SETTING: General practices contributing data to the UK Clinical Practice Research Database. PARTICIPANTS: 39,980 people with an incident diagnosis of alcohol dependence aged 16 years or older between 1 January 1990 and 31 December 2013. MAIN OUTCOME MEASURE: Use of pharmacotherapy (acamprosate, disulfiram, naltrexone, baclofen and topiramate) to promote abstinence from alcohol or reduce drinking to safe levels in the first 12 months after a recorded diagnosis of alcohol dependence. FINDINGS: Only 4,677 (11.7%) of the cohort received relevant pharmacotherapy in the 12 months following diagnosis. Of the 35,303 that did not receive pharmacotherapy, 3,255 (9.2%) received psychosocial support. The remaining 32,048 (80.2%) did not receive either mode of treatment in the first 12 months. Factors that independently reduced the likelihood of receiving pharmacotherapy included: being male (Odds Ratio [OR] 0.74; 95% CI 0.69 to 0.78); older (65-74 years: OR 0.61; 95% CI 0.49 to 0.77); being from a practice based in the most deprived quintile (OR 0.58; 95% CI 0.53 to 0.64); and being located in Northern Ireland (OR 0.78; 95% CI 0.67 to 0.91). The median duration to initiation of pharmacotherapy was 0.80 months (95% CI 0.70 to 1.00) for acamprosate and 0.60 months (95% CI 0.43 to 0.73) for disulfiram. Persistence analysis for those receiving acamprosate and disulfiram revealed that many patients never received a repeat prescription; persistence at 6 months was 27.7% for acomprosate and 33.2% for disulfiram. The median duration of therapy was 2.10 months (95% CI 1.87 to 2.53) for acamprosate and 3.13 months (95% CI 2.77 to 3.36) for disulfiram. CONCLUSION: Drug therapy to promote abstinence in alcohol dependent patients was low, with the majority of patients receiving no therapy, either psychological or pharmacological. When drug therapy was prescribed, persistence was low with most patients receiving only one prescription. Our data show that treatment for alcohol dependence is haphazard, and there is an urgent need to explore strategies for improving clinical management of this patient group.